THE INTERPRETATIONS OF QURAN SURAH AN-NISA (4): 3 BY IBN JARIR AL-TABARI IN JAMI‘ AL-BAYAN FI TA’WIL AL-QUR’AN AND ABU LAYTH AL-SAMARQANDI IN BAHR AL-‘ULUM: Penafsiran Ibnu Jarir Ath-Thabari dalam Tafsir “Jami’ul Bayan fii Ta’wilil Qur’an” dan Abu Layts As-Samarqandi dalam Tafsir “Bahrul Ulum” Terhadap Q.S An-Nisa’ ayat 3 - Pendi Nurul Azmi; R. Edi Komarudin; Asep Ahmad Fathurahman (Senarai: Journal of Islamic Heritage and Civilization, 2026)
Qur’anic interpretation is a continuous scholarly endeavor to elucidate divine guidance in response to evolving social contexts through both classical and contemporary approaches. This study examines the interpretations of Q.S. An-Nisāʾ (4):3 by two prominent exegetes, Ibn Jarīr al-Ṭabarī in Jāmiʿ al-Bayān fī Taʾwīl al-Qurʾān and Abū Layth al-Samarqandī in Baḥr al-ʿUlūm, employing a tafsīr muqāran (comparative exegesis) method to identify similarities, differences, and underlying methodological orientations. The findings demonstrate that Ibn Jarīr al-Ṭabarī adopts a strong riwāyah-based approach, presenting extensive narrations from the Companions and Successors and emphasizing justice as the fundamental condition for marrying more than one woman. In contrast, Abū Layth al-Samarqandī prioritizes a practical fiqh-oriented perspective, offering concise and accessible explanations intended for broader audiences. Despite these methodological differences, both exegetes concur that the verse underscores the imperative to avoid injustice toward orphan girls due to their vulnerability, while simultaneously warning against injustice toward other women in marriage. This study affirms the significance of comparative Qur’anic interpretation in enriching contemporary discussions on polygamy by reaffirming justice as the core ethical principle underlying Islamic law.